2018
DOI: 10.1002/hep.30228
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Endotoxin on Type 3 Inositol 1,4,5‐Trisphosphate Receptor in Human Cholangiocytes

Abstract: Clinical conditions that result in endotoxemia, such as sepsis and alcoholic hepatitis, often are accompanied by cholestasis. Although hepatocellular changes in response to lipopolysaccharide (LPS) have been well characterized, less is known about whether and how cholangiocytes contribute to this form of cholestasis. We examined effects of endotoxin on expression and function of the type 3 inositol trisphosphate receptor (ITPR3), because this is the main intracellular Ca release channel in cholangiocytes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 44 publications
4
53
0
Order By: Relevance
“…A). In liver biopsies obtained from controls, quantitative confocal immunofluorescence showed that ITPR3 expression in cholangiocytes was low and was concentrated in the apical region, as has been described, whereas labeling of ITPR3 in cholangiocytes was significantly more intense in patients with hilar CCA or iCCA (Fig. A‐C).…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…A). In liver biopsies obtained from controls, quantitative confocal immunofluorescence showed that ITPR3 expression in cholangiocytes was low and was concentrated in the apical region, as has been described, whereas labeling of ITPR3 in cholangiocytes was significantly more intense in patients with hilar CCA or iCCA (Fig. A‐C).…”
Section: Resultssupporting
confidence: 66%
“…Both cell proliferation and progression through the cell cycle depend on Ca 2+ signals in the nucleus in particular, so the nuclear‐targeted fluorescent calcium sensor GCaMP3 was used to specifically determine the role of ITPR3 in Ca 2+ signaling in the nucleus. MzCha1 cells were stimulated with extracellular adenosine triphosphate (ATP; 20 μM) because cholangiocytes express P2Y receptors that link to inositol trisphosphate (IP 3 )‐mediated Ca 2+ signaling . ATP consistently increased Ca 2+ in the nucleoplasm of control cells, but nuclear Ca 2+ signals were minimal to absent in ITPR3‐KO cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations